Household access to microcredit and child work in rural Malawi - Gautam Hazarika; Sudipta Sarangi (Institute for the Study of Labor (IZA), 2005)
This paper examines the effect of household access to microcredit upon work by seven to eleven year old children in rural Malawi. Given that microcredit organizations foster household enterprises wherein much child labor is engaged, this paper aims to discover whether access to microcredit might increase work by children. It is found that household access to microcredit, measured in a novel manner as self-assessed credit limits at microcredit organizations, raises the probability of child work in households with sample mean values of land ownership and number of retail sales enterprises. It appears this is due to children having to take up more domestic chores as adults are busied in household enterprises following improved access to microcredit.
Keywords: J22; 330; child labor; microcredit; Kinderarbeit; Privater Haushalt; Ländlicher Raum; Malawi; Mikrofinanzierung